Assessment of Vibration Frequencies of Piezo-Actuated Panel by Model-Assisted Self-Mixing Interferometry - E. Bodo; L. Ciccarelli; V. Bello; S. Morganti; S. Merlo (IEEE Open Journal of Instrumentation and Measurement)
Flat surfaces driven by attached piezoelectric actuators are promising devices for the development of future generations of speakers. Although audio devices characterization requires sound pressure level measurements, preliminary testing of electromechanical frequency response and actuation efficiency may provide meaningful insights into the operation capability of these innovative systems. In this work, we have investigated a Plexiglas panel attached to a piezo-ceramic actuator as test structure. In particular, we successfully combined finite element analysis and out-of-plane displacement measurements performed with a semiconductor laser feedback (or self-mixing) interferometer in a few selected spots of the optically diffusing panel. To rapidly detect the spectral response, the actuator was driven by electrical white noise to obtain a photodetected interferometric signal in the frequency domain directly proportional to the vibration amplitude. Sinusoidal driving of the actuator at selected frequencies and interferometric signal analyses in the time domain allowed quantifying the actuation efficiency, as a function of the frequency and of the position on the panel, of the three mechanical modes exhibiting out-of-plane displacement in the range up to approximately 1 kHz. The values of natural frequencies numerically obtained match the experimentally detected values, with a difference up to 3%, 6%, and 9% for Mode 1, Mode 4, and Mode 8, respectively, that are the three lowest modes with effective modal mass along the z-direction.